Environmental and host factors underlying tick infestation in invasive raccoons (Procyon lotor) in Hokkaido, Japan - Ito, Mebuki; Minamikawa, Miku; Kovba, Anastasiia; Numata, Hideka; Itoh, Tetsuji; Katada, Yuki; Niwa, Shiho; Taya, Yurie; Shiraki, Yuto; Pandey, Gita Sadaula; Kelava, Samuel; Nonaka, Nariaki; et al. (Ticks and tick-borne diseases, 2024)
Revealing interactions between ticks and wild animals is vital for gaining insights into the dynamics of tick-borne pathogens in the natural environment. We aimed to elucidate the factors that determine tick infestation in wild animals by investigating ticks on invasive raccoons (Procyon lotor) in Hokkaido, Japan. We first examined the composition, intensity, and seasonal variation of ticks infesting raccoons in six study areas in Hokkaido from March 2022 to August 2023. In one study area, ticks infesting tanukis (raccoon dog, Nyctereutes procyonoides albus) were collected in May to July in both 2022 and 2023, and questing ticks were collected from the vegetation by flagging every other week in the same period. Next, we screened 17 environmental and host variables to determine factors that affect the number of ticks infesting raccoons using generalized linear (mixed) models. From 245 raccoons, we identified a total of 3,917 ticks belonging to eight species of two genera: the most prominent species were Ixodes ovatus (52.9 %), followed by Haemaphysalis megaspinosa (14.4 %), Ixodes tanuki (10.6 %), and Ixodes persulcatus (9.5 %). Ixodes ovatus was also predominant among questing ticks and ticks infesting tanukis. Although I. tanuki was frequently collected from raccoons and tanukis, it was rarely collected in the field. The variables that significantly affected the infestation on raccoons differed by genus, species and developmental stage of the tick. For instance, the infestation of adult I. ovatus was significantly affected by four variables: night-time temperature during nine days before capturing the raccoon, the size of forest area around the capture site, sex of the raccoon, and sampling season. The first two variables were also responsible for the infestation on raccoons of almost all species and stages of ticks. Our study revealed that the number and composition of ticks infesting raccoons can be affected not only by landscape of their habitats but also by weather conditions in several days before capturing.